So this function is given:


I have to calculate its Taylor series around $x=1$ and use it in some way to calculate the following sum:

$$\sum_{n=1}^{\infty} \frac{n+2}{(2n)!!}$$

I do know the fact: $$(2n)!!=2^nn!$$ $$\sum_{n=1}^{\infty} \frac{n+2}{(2n)!!}=\sum_{n=1}^{\infty} \frac{n+2}{2^nn!}$$

And after 1st step of taylor series i get this:

$$f(x)=(x-1)\sum_{n=0}^{\infty} \frac{(-2(x-1))^n}{n!}= \sum_{n=0}^{\infty} \frac{(-1)^n2^n(x-1)^{n+1}}{n!} = -1 + \sum_{n=1}^{\infty} \frac{(-1)^{n}2^n(x-1)^{n+1}}{n!} $$

But I have no idea what to do next. Any help would be appreciated.

  • 1
    $\begingroup$ Well, It seems easier to separate the sum into the sum of $\frac n{2^nn!}$ and $\frac 2{2^nn!}$. $\endgroup$ – lulu Jun 21 at 13:51
  • $\begingroup$ That's the Taylor series of $f(x-1)$ isn't it? Note that $f(1)=e^{-2}$, so the constant term is incorrect. $\endgroup$ – saulspatz Jun 21 at 13:58
  • $\begingroup$ How should I fix it? $\endgroup$ – MathIsTheWayOfLife Jun 21 at 14:06
  • $\begingroup$ Well, you have to actually calculate the Taylor series. I don't know what it is off the top of my head. $\endgroup$ – saulspatz Jun 21 at 14:34


To calculate the Taylor series of $f$, start by calculating the Taylor series of $g(x)=e^{-2x}$. Obviously, $g^{(n)}(x)=(-2)^ne^{-2x}$ so $g^{(n)}(1)=(-2)^ne^{-2}$ and $$g(x)=\sum_{n=0}^\infty(-2)^ne^{-2}(x-1)^n$$ is the Taylor series of $g$ about $x=1$.

Now $f(x)=xg(x)=(1+(x-1))g(x)$, so you can easily get the Taylor series for $f$ about $x=1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.